POLYGAMY IN FOCUS: A DISCOURSE ON SOCIETAL NORMS, RIGHTS, AND PRACTICAL CHALLENGES - Sereikaitė Motiejūnė, Gintarė (PEOPLE: International Journal of Social Sciences, 2024)
This article delves into the multifaceted perspectives on polygamy, specifically focusing on why a woman might opt to become a co-wife. The study, conducted in a private Facebook group for women who are part of or interested in polygamous relationships, unveils that societal norms, religious convictions, and individual situations greatly shape the views on polygamy. Despite certain muslim feminist groups advocating for the restriction of polygamy to specific scenarios, both men and women have their unique interpretations and applications of the principle, often extending beyond the confines of the Qur'anic context. However, these theories don't fully encompass the practical responsibilities and potential hurdles tied to polygamy. The study also exposed that polygamy, commonly perceived from a male-centric viewpoint, could also be interpreted as a woman's right, particularly when she is the instigator of the marriage. In summary, the research provides both theoretical insights and pragmatic implications, allowing us to perceive polygamy not just as a male prerogative but also as a potential social support structure for women.